Drug retention rates of second biologic agents after switching from tumor necrosis factor inhibitors for rheumatoid arthritis in Japanese patients on low-dose methotrexate or without methotrexate. Issue 2 (March 2015) - Kobayakawa, Tomonori; Kojima, Toshihisa; Takahashi, Nobunori; Hayashi, Masatoshi; Yabe, Yuichiro; Kaneko, Atsushi; Shioura, Tomone; Saito, Kiwamu; Hirano, Yuji; Kanayama, Yasuhide; Miyake, Hiroyuki; Asai, Nobuyuki; et al.
Abstract Objectives. The purpose of this study was to explore drug retention rates of second biologic agents after switching from tumor necrosis factor inhibitors (TNFi) in clinical practice in patients with rheumatoid arthritis (RA) on low-dose methotrexate (MTX) or without MTX. Methods. A total of 169 RA patients who had been withdrawn from first-course TNFi therapy and received a different TNFi or tocilizumab (TCZ) as a second biologic agent were selected from the Tsurumai Biologics Communication Registry, an observational cohort database. Retention rates of second biologic treatment were compared by the type of first TNFi and second biologic agents. Results. Eighty-six patients received first-course infliximab (IFX) or adalimumab (ADA) therapy, and 83 patients received first-course etanercept (ETN) therapy. The former group had a significantly higher retention rate (IFX, 81.1%; ADA, 83.3%) of the second biologic therapy compared to the latter (56.6%, p < 0.001, log-rank test). Drug retention rates of the second biologic agent after switching from IFX/ADA were significantly higher with ETN (90.0%) and TCZ (94.7%) than with ADA/IFX (59.3%). Drug retention rates of the second biologic agent after switching from ETN were significantly higher with TCZ (75.9%) than with ADA/IFX (46.3%). The differences were significant even after adjusting for baseline clinical variables using the Cox proportional hazards model. Conclusions. Drug retention rates of IFX and ADA after switching from the first TNFi were significantly lower compared to those of ETN and TCZ in patients on low-dose MTX or without MTX.